2020
DOI: 10.3390/mi11100930
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Ultra-Wideband Hybrid Metamaterial Based Microwave Absorber

Abstract: In this paper, we propose a novel design of an ultra-wideband hybrid microwave absorber operating in the frequency range between 2 GHz and 18 GHz. This proposed hybrid absorber is composed of two different layers that integrate a multiband metamaterial absorber and a lossy dielectric layer. The metamaterial absorber consists of a periodic pattern that is composed of an arrangement of different scales of coupled resonators and a metallic ground plane, and the dielectric layer is made of epoxy foam composite loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 60 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…The absorber, designed and fabricated using LDW, has the widest bandwidth reported thus far, with the lowest thickness in the low-frequency band. Figure 13 presents a comparison of the fractional bandwidth and relative thickness (relative thickness = thickness/λ L , where λ L is the wavelength corresponding to the minimum operating frequency) of conventional, metamaterial [13,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], and proposed absorbers, thus demonstrating the improvement in the microwave absorption achieved by the metamaterial designed and achieved through LDW.…”
Section: Comparison Of Microwave Absorption Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorber, designed and fabricated using LDW, has the widest bandwidth reported thus far, with the lowest thickness in the low-frequency band. Figure 13 presents a comparison of the fractional bandwidth and relative thickness (relative thickness = thickness/λ L , where λ L is the wavelength corresponding to the minimum operating frequency) of conventional, metamaterial [13,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], and proposed absorbers, thus demonstrating the improvement in the microwave absorption achieved by the metamaterial designed and achieved through LDW.…”
Section: Comparison Of Microwave Absorption Performancesmentioning
confidence: 99%
“…Pan et al reported the application of rGO laminates for ultra-wideband microwave absorption and demonstrated that a coating with a thickness of over 30 mm provided efficient absorption in the range of 2-10.8 GHz, which hindered its conformal and miniature applications [46]. Assal et al demonstrated a multiband hybrid layer metamaterial-based array for a microwave absorber, with an absorber thickness of approximately 16.2 mm and a high absorption performance of greater than 95% from 2.6 GHz to 18 GHz [47]. However, its low cutoff frequency of 2.6 GHz did not fully cover the S-band, which is crucial for wireless communication and radar applications.…”
Section: Comparison Of Microwave Absorption Performancesmentioning
confidence: 99%
“…Until recently, there have been a number of investigations on microwave absorbers comprising of varying absorption levels, bandwidth and polarization independency over a wide-ranging angle of incidence with various thicknesses and few other parameters in different frequency ranges [78][79][80][81][82][83][84][85][86][87][88].…”
Section: Conformabilitymentioning
confidence: 99%
“…This is used to achieve lower frequency band applications such that Bluetooth etc. The peak gain of 4.4 dB by using this implementation was measured [7]. Dielectric resonator fabricated which helps to increase gain and e ciency in this simulation two cylindrical holes were inserted over the antenna into the dielectric resonator thus 4.79 dB gain was the peak gain was measured by the author [8].…”
Section: Introductionmentioning
confidence: 99%